Brain MRI and single photon emission computed tomography in severe athetotic cerebral palsy: a comparative study with mental and motor disorders - Yamada, K; Tsuzura, S; Matsuda, H (No to hattatsu, 1995)
Single photon emission computed tomography (SPECT) using N-isopropyl-p-[123I]-iodoamphetamine(123I-IMP) was performed in twelve patients with severe athetotic cerebral palsy (Ath; 5 males and 7 females) who had both motor delay (unable to move) and mental retardation (I.Q, or D.Q, below 30). The neuroimaging findings of those patients were compared with those of patients mental and motor disorders. In five cases suffering from neonatal asphyxia, SPECT demonstrated a decreased regional cerebral blood flow (rCBF) in corpus striatum, thalamus, orbitofrontal areas, pericentral gyrus areas, prefrontal areas and medial temporal areas. In seven cases suffering from neonatal jaundice, SPECT demonstrated a decreased rCBF in orbito-frontal areas, prefrontal areas and medial temporal areas. SPECT showed hypoperfusion of peri-central gyrus areas in cases with complications of spastic palsy. The decreased rCBF in medial temporal areas mostly corresponded to an alteration in hippocampal formation as assessed by magnetic resonance imaging (MRI). Cases with hypoperfusion of bilateral medial temporal areas showed a lower score of language understanding than those with the unilateral damage. In cases with hypofusion of bilateral prefrontal areas and bilateral medial temporal areas, the grade of understanding of language was almost below 12 months. In cases with hypoperfusion of orbitofrontal areas, psychomotor hypersensitivity had been observed. Those results suggest that IMP-SPECT and MRI of the brain is useful tool for neurological assessment in handicapped patients with athetotic cerebral palsy.